Length Weight Relationship of Whip Fin Silver Biddy Gerres Filamentosus (Cuvier) from Sharavathi Estuary, Central West Coast Of India - and Bhat U. G2, Renuka G1*, (Recent Research in Science and Technology, 2011)
The length weight relationship and relative condition factors were studied between Jan. and Dec. 2008. Length weight relationship of Gerres filamentosus did not differ significantly between the sexes and combined equation is given by W= 0.000001663 L3.1675. The highest Kn value in female was in June (1.0950) and lowest in July (1.0950). Similarly the highest Kn value in male was in Dec (1.0587) and lowest in July (0.8994). Both in males and females the Kn value was highest in the size of 101-110 mm which can be attributed to feeding.